Corporate art collections a handbook to corporate buying - Appleyard, Charlotte; Salzmann, James; Sotheby's (Firm). Institute of Art. (Farnham, United Kingdom Burlington, Vermont Lund Humphries in association with Sotheby's Institute of Art, 2012)
This volume offers a guide to corporate collecting, examining its history, nature and importance, and the different reasons for starting and maintaining corporate collections.
Introduction : The development of the modern corporate collection -- Part I. The collections : Beginning our tour ; Group 1. Emblematic collections : Aspen Insurance Holdings Limited; Standard Bank; General Mills; Cazenove & Co. ; Group 2. Environmental enrichment : Deloitte (London); Pictet & Cie; Deutsche Bank; SImmons & Simmons; Hiscox ; Group 3. Patronage : Abraaj Capital; Deloitte (Luxembourg); British Airway ; Group 4. All-rounders : Progressive Insurance; Louis Vuitton; Monsoon -- Part II. Change, crisis, finance and what lies beyond : The art of disposals / Catherine Higgs ; Dispersal case study: The Sara Lee Collection ; The art of taxes / Catherine Higgs and James Salzmann ; Dispersal case study: The Fleming Collection -- Starting a corporate collection -- Appendix : Selected interviews with consultants and artists.
Keywords: Corporations -- Art collections; Corporations -- Art collections -- Case studies; Art museums -- Collection management; Art museums -- Collection management -- Case studies; Art patronage